The Realization of Directive Speech Act by Da’i on Dialogic Da’wah in Kota Surakarta: A Socio-Pragmatic Study - nugroho, Miftah; Purnanto, Dwi; Tarjana, Sri Samiati (Komunitas, 2018)
This article aims at explaining the directive speech acts realization on QA sessions of a dialogic situated communication. The directive speech requires a communicative counterpart (to do something as the speaker’s wishes) by his/her words. Under the Sociopragmatic is the crossdisciple study between the pragmatic and sociological disciplines. The data were obtained by applying methods of observation and recording. The data source of this study took the Islamic liturgical dialogues dakwah held by both Islamic organizations and Islamic sermons held at schools, homes, or mosques. The result shows that, in terms of the communicative functions, the directive speech acts were realized from the acts of suggesting, and warning, a da’i or preachers are adhering to the principle of harmony as reflected from their commitment towards the observed maxims of kurmat, andhap asor and the tepa slilra.